AN EXPLORATORY POST-OCCUPANCY ASSESSMENT OF SMART BUILDING TECHNOLOGIES IN OWNER-OCCUPIED HOUSING IN A DEVELOPING URBAN CONTEXT - Ugochukwu, Precious Juliet; Edicha, Joseph Ojoma; Inobeme, Ferdinand Ozemoya (FUDMA Journal of Sciences, 2026)
This study examined the awareness, adoption patterns, and post-occupancy performance of smart home technologies in owner-occupied residential buildings. A questionnaire survey was administered to 68 homeowners, and the data were analyzed using descriptive and inferential statistical methods, including frequency distribution, chi-square analysis, and ANOVA. The findings revealed relatively high awareness of smart home technologies, with 67.6% of respondents indicating prior knowledge of smart homes. However, awareness of specific smart features varied considerably, suggesting uneven technical understanding of integrated smart systems. Smart technology adoption was predominantly retrofit-based, with 62.0% of installations introduced after occupancy rather than during the design or construction stages. This indicates limited incorporation of smart infrastructure considerations during initial building development. User satisfaction with installed smart systems was generally high, as 82.2% of respondents reported being satisfied or very satisfied with their systems. In contrast, perceptions regarding energy reduction were more varied: only 35.0% reported significant or very significant energy savings, while 21.7% perceived no reduction in energy consumption. This divergence suggests that homeowners may value smart technologies more for convenience, security, automation, and improved occupant interaction than for demonstrable energy-efficiency outcomes. Inferential analysis revealed no statistically significant relationship between educational qualification and timing of smart technology adoption, nor between building type and perceived energy reduction. The study concludes that smart home adoption is driven more by user experience and convenience than verified energy-performance outcomes, highlighting the need for better system integration and design-stage planning. Future studies should incorporate objective post-occupancy energy data to complement perception-based assessments.
Keywords: Smart home technologies; post-occupancy performance; retrofit adoption; energy perception; user satisfaction; smart system integration